Acute effects of plyometric-based conditioning activity and warm-up music stimuli on physical performance and affective state in male taekwondo athletes - Messaoudi, Hamdi; Ouergui, Ibrahim; Delleli, Slaheddine; Ballmann, Christopher Garrett; Ardigò, Luca Paolo; Chtourou, Hamdi (Frontiers in Sports and Active Living, 2024)
Introduction This study assesses the acute effects of combining a plyometric-based conditioning activity (CA) with different musical stimuli during warm-up on taekwondo (TKD) performance and related psychological aspects. Methods In a randomized cross-over study design, 16 male TKD athletes (age: 19.94 ± 1.12 years) performed the TKD-specific agility test (TSAT), frequency speed of kick test (FSKT-10s) and its multiple version (FSKT-mult) under 7 experimental and one control condition. For the experimental conditions, participants experienced varying combinations of music selection process [self-selected (SSM) vs. pre-selected (PSM)], and music tempo [fast (F) vs. slow (S)], within preferred (PG) and non-preferred (NPG) music genre; all in the presence of a plyometric based-CA. Athletes were instructed to rate their perceived exertion (RPE) after each test and their felt arousal (FAS), feeling scale (FS), and motivation after testing completion. Results Findings showed that combining a plyometric-based CA with SSMPG at both fast and slow tempo improved TSAT, FSK-10s, FSKT-mult, FAS, motivation, and RPE post-TSAT greater than the other conditions (all p < 0.05). Additionally, FSSMPG combined with CA improved FS, and RPE after both FSKT-10s and FSKT-mult better than the other conditions (all p < 0.05). Conclusion In conclusion, listening to fast self-selected music from a preferred genre in combination with a plyometric-based CA during warm-up setups an individualized warm-up strategy and serves to improve the subsequent specific performances and the related psychological aspects in TKD athletes.